Efficient performance of locally processed serum in vero cell culture - Ahmad Nor, Yusilawati; Jaafar, Nuhu Jaafar; Mel, Maizirwan (David Publishing, 2011)
Serum is a vital supplement in animal cell culture. Serum used in animal cell culture is from bovine source marketed by different companies, and somewhat expensive. The aims of this work were serum treatment and screening for the best serum concentration for Vero cell culture using STATISTICA software. The best result obtained from the software was used to compare with different commercial serum (GIBCOTM and PAA). Local serum was prepared first by aseptically collecting 500 mL whole blood from disease free cattle using 50 mL anticoagulant free centrifuge tubes. Whole blood was centrifuged to separate serum and blood cells. Serum collected was treated with ultraviolet radiation and heat inactivated for 30 min at 56 °C. Vero cells were cultured in 25 cm2 Tflasks with an initial cell seeding of 4.2 × 105 cells/mL. Results obtained showed that locally made serum is comparable in terms of maximum viable cell numbers (8.0 × 105 cells/mL) compared to commercial bovine serum (8.5 × 105 cell/mL and 6.78 × 105 cell/mL) for GIBCO and PAA respectively after four days. From the study, locally prepared serum can be substituted to the commercial sera for Vero cell culture.